(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
A total of 570 herbivorous fishes (Sarpa salpa, Siganus luridus and Siganus rivulatus) were collected from the western coast of Libya during the period from May 2013 to June 2014. Samples were taken directly from fishermen then transferred to the laboratory in Marine Biology Research Center, in order to take different measurements such as; total length and total weight for each fish. Livers and stomachs have been taken and weighed. The results showed that in the herbivores fishes, S. luridus was more abundant, shows more ability to occupating the niche, and compete the other herbivores fishes. Moreover, this study showed that the seagrass and algae are important diet for both species; also there is no high competition between these species in this area of the south Mediterranean. This study tried to fill the gap of knowledge and document some important biological aspects on both species in Libyan waters.